PENGARUH METODE PEMBELAJARAN JOYFULL LEARNING BERBANTUAN MEDIA KIT EKSPERIMEN SEDERHANATERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPAS SDN 01 KARANG ANYAR LAMPUNG SELATAN - Rahmawati, Emi; Chairul Amriyah; Deri Firmansah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research focuses on evaluating the effect of joyful learning combined with a simple experimental kit on the learning interest og grade IV students in science at SDN 01 Karang Anyar, South Lampung. The study was motivated by students weak learning interest, which can be seen from their limited engagement, attention also enthusiasm during classroom activities. This study used a quantitative approach with a quasi experimental research design. The research population consisted of 83 fourth-grade students, while the sample included 56 students selected and divided into a group receiving treatment also control group. The data collection method included questionnaires, observation techniques also documentation. A validated and reliable learning interest questionnaire was employed as the research instrument. The data were analyzed through initial requirement tests, including normality also homogeneity, and subsequently continued with an independent samples t-test was used for hypothesis testing, also the results demonstrated a statistically significant influence of the joyful learning method assisted by simple experimental kit media on students’ the results demonstrated a significant influence on learning interest, iindicated by the alternative hypothesis is accepted due to the p-value being lower than 0.05. In conclusion , applying the joyful learning strategy supported by simple experimental kit media demonstrates effectiveness in improving students learning interest in the IPAS subject.